Laser and electron beam-induced formation of Ag/Cr structures on Ag 2 CrO 4 - Lemos, P. S.; Silva, G. S.; Roca, R. A.; Assis, M.; Torres-Mendieta, R.; Beltrán-Mir, H.; Mínguez-Vega, G.; Cordoncillo, E.; Andrés, J.; Longo, E. [UNESP] (Royal Society of Chemistry (RSC), 2019)
The interactions of silver chromate (Ag 2 CrO 4 ) with a femtosecond (fs) laser and electron beam irradiations were investigated. For the first time, the growth and coalescence of metallic Ag nanoparticles (NPs) on an Ag 2 CrO 4 surface via fs laser irradiation can be reported. Furthermore, electron beam irradiation causes a segregation process of Ag NPs in which Ag nanofilaments are obtained. The Ag 2 CrO 4 particles were characterized using X-ray diffraction (XRD), micro-Raman spectroscopy (Raman), field-emission scanning electron microscopy (FE-SEM), high-resolution electron microscopy, and energy-dispersive X-ray spectroscopy (EDS). According to the results, the fs/electron beam irradiations of Ag 2 CrO 4 are environmentally friendly, fast, and effective methods to produce metallic Ag NPs. Both strategies have enormous potential for the synthesis and morphological control of Ag NPs on templates or biotemplates, core-shells, decorations, and composites based on Ag 2-x CrO 4 :Ag materials, which are difficult to synthesize using conventional chemical and physical methods.